2019
DOI: 10.1002/ldr.3329
|View full text |Cite
|
Sign up to set email alerts
|

Water or soil—What is the dominant driver controlling the vegetation pattern of degraded shallow mountain peatlands?

Abstract: The aim of this paper was to evaluate the link between environmental conditions and the vegetation pattern of mountain peatlands drained for forestry. We assumed that (a) water chemistry and soil properties differ between the investigated peatlands types—from fen to bog, (b) the vegetation pattern is dependent on water chemistry and soil properties, and (c) water chemistry and soil properties play different roles in determining peatland patterning. For our study, five ecologically and topographically diverse f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…The obtained data imply that those smaller mires originated in the middle to late Holocene (between 3301 BC to AD 1137 according to radiocarbon dating), and that there was a strong human impact on vegetation since the Middle Ages, enhanced by a drainage network built in the 19th century. Soil studies carried out by [26,27,[29][30][31][32] revealed internal layering of the phytogenic sediments and their degradation due to draining of the mires. Since all those studies provided information on mire subsurface structure limited to randomly located boreholes, the actual morphology of the phytogenic sediment basement and their internal structure remain unknown.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained data imply that those smaller mires originated in the middle to late Holocene (between 3301 BC to AD 1137 according to radiocarbon dating), and that there was a strong human impact on vegetation since the Middle Ages, enhanced by a drainage network built in the 19th century. Soil studies carried out by [26,27,[29][30][31][32] revealed internal layering of the phytogenic sediments and their degradation due to draining of the mires. Since all those studies provided information on mire subsurface structure limited to randomly located boreholes, the actual morphology of the phytogenic sediment basement and their internal structure remain unknown.…”
Section: Study Areamentioning
confidence: 99%
“…As a consequence of climate change and draining, mires have become more susceptible to wildfires, which are especially difficult to tackle when smouldering fires develop [6,7]. The need for protection of wetlands is undisputable at present, and efforts are being made to restore local hydrological systems and original ecosystems, e.g., by damming drainage ditches, as has occurred in the Stolowe Mountain National Park area in Poland [8,9]. One of the key problems in the protection and restoration of drained mires is that anthropogenic changes have obliterated their morphological and environmental features, making their original boundaries difficult to determine in the field.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, peat soils characterized by low mineral nutrient content, low pH, low soil oxygen content and high soil water content enhance plant communities dominated by peat mosses (Sphagnum spp.) (Bragazza and Gerdol, 2002;Glina et al, 2019;Bengtsson et al, 2021).…”
Section: Soil Oxygen Soil Ph Nutrient Contents and Litterfall Qualitymentioning
confidence: 99%
“…Within peat ecosystems, many community activities are carried out, especially those that are related to the social economy. Related research results were carried out [14,15,[19][20][21][22][23]. Regarding land conservation and management, research that has been carried out include studies [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%